(untitled) (INNOTEC, 2019)
Whey proteins are heated during production of infant formulae. The denaturation and aggregation of whey proteins can reduce their solubility, with functional, technological and nutritional implications. In the current work, the effect of heat treatment and presence of casein, lactose and inulin, at the proportions used during production of infant formula, on the protein solubility, was studied. Aqueous WPI dispersions with or without calcium caseinate (CAS), inulin (INUL) and lactose (LAC), were prepared. Unheated (UH) and heated (HT) dispersions at 66, 75 and 85ºC for 30 and 60 min were analyzed. The UH systems with the highest solubility were WP (89.3±2.0 %) and WP-INUL (89.6±1.8 %). Solubility of WP decreased with HT from 75ºC-30 min, reaching the minimum solubility (41.7±1.2 %) after 85ºC-60 min. WP-INUL showed the same trend. Solubility of WP-LAC decreased with HT, although the solubility loss after HT 75ºC-60 min was lower than in the system without lactose. CAS presence prevented the loss of protein solubility, which increased with HT until 75ºC-60 min (reaching 100 % in the WP-CAS system).